Pulmonary rehabilitation in chronic obstructive pulmonary disease - Araújo, Cintia Laura Pereira de (2014)
Introduction: The chronic obstructive pulmonary disease (COPD) impairs the functional status with consequent impairment of the activities of daily living (ADL). This study aimed to investigate the effect of a long term pulmonary rehabilitation (PR) on the functional status, dyspnea and on the BODE index in patients with COPD. Case report: This is a retrospective and descriptive study. The records of five patients that participated in a year PR program were analyzed. Assessments about spirometry, body mass index (BMI), London Chest Activity of Daily Living (LCADL) and Medical Research Council (MRC) scales and six-minute walking test (6MWT) were collected. After a year participating in the PR program, most patients improved their functional capacity, dyspnea and reduced the risk of mortality. Conclusion: A year of PR seemed to maintain the improvement in functional capacity obtained after 24 training sessions in patients with COPD.